Book Review: K. P. Kannan, Interrogating Inclusive Growth: Poverty and Inequality in India. (June 2016) - Abraham, Dimple Tresa
K. P. Kannan, Interrogating Inclusive Growth: Poverty and Inequality in India . New Delhi: Routledge, 2014, 310 pages, ₹795, ISBN 978-1-138-79565-5